The Effects of HMP and TPP on Political Participation in the Partisan Media Context - Hyun, Ki Deuk and Seo, Mihye (Communication Research, 2021)
Scholars suggest that hostile media perception (HMP) and third-person perception (TPP) can motivate people to take political action to counteract the unwarranted influence of slanted media. Little research has been undertaken, however, regarding how HMP and TPP relate to political participation in partisan media settings in which news media hold specific partisan or ideological inclinations. This study explored HMP and TPP of partisan media and their associations with political participation in South Korea, which has a strongly partisan media system. Findings indicate that partisans tend to have strong HMP and TPP of antagonistic partisan media. Interestingly, progressives’ HMP and TPP of hostile conservative media were stronger than conservatives’ HMP and TPP of progressive media. Accordingly, HMP and TPP of conservative media were more strongly associated with political participation than HMP and TPP of progressive media. The political and media contexts of a specific country that might shape the relationships among HMP, TPP, and political participation are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE4ODIwMjI5